EFEKTIVITAS PEMBELAJARAN STATISTIK KELAS IX SMP MELALUI MODEL PEMBELAJARAN KOOPERATIF - Fitri Era Sugesti (Universitas Muhammadiyah Pringsewu, 2016)
The strategy and teaching technique are needed by each teacher in order to obtain the maximum learning achievement. However, it does not appropriate with the fact, learning achievement result on Statistics material, only 9 students from 30 students who achieve the minimum learning completeness score 7. One of the efforts makes it done in solving the problem is using cooperative learning model. This study aims to determine the effectiveness of statistic materials of third grade students through cooperative learning model. This study is comparative study. The population was all of the third grade students at SMP N 1 Kota Agung Timur in the academic year 2013-2014. Based on the hypothesis testing result, it proven that cooperative learning model is effective to complete the student learning achievement of the third grade students in statistics material. So, cooperative learning model can complete the statistics students learning achievement of the third grade students at SMP N 1 Kota Agung Timur in the academic year 2013- 2014. Keywords : effectiveness, cooperative learning, learning achievement result